AN ANALYSIS OF THE LEXICAL AMBIGUITY USED IN COCO MOVIE SCRIPT - Faina, Ratih; Rositasari, Tri; Elfarissyah, Andriamella (Universitas Muhammadiyah Palembang, 2021)
The objectives of this study were to describe the form of homonym of the lexical ambiguity and to analyze the most dominant of homonym of the lexical ambiguity that used in Coco movie script by Lee Unkrich and Adrian Molina. In analysis of lexical ambiguity, it just focused on homonym that used by Miguel as the main character from the movie script. This study used a descriptive qualitative research and it was obtained by using documentation method and the conversation of movie script as a research instrument. The conversation of Coco movie script was used to identify and get information about homonym, it showed that there were two forms of homonym in lexical ambiguity that used in Coco movie script and they were homophone and homograph. Based on the result of data, it was found that there were 987 conversations of Coco movie script both in homophone and homograph. From 987 conversations of Coco movie script, it can be said that 226 conversations used the homophone words, it consisted of 70 homophone words and it occurred in 645 times. Then, 70 conversations used the homograph words, it consisted of 29 homograph words and it occurred in 06 times. So, it can be concluded that the most dominant of homonym forms of lexical ambiguity in Coco movie script was homophone which consisted of 70 words and it occured in 645 times.